Marketing Strategy Analysis using SOAR and QSPM Methods in PT Cicil Solusi Mitra Teknologi - Rahmawati, Betty; Minto Waluyo (KINERJA, 2023)
Technology development is so rapid in the era of society 5.0, one of which is a financial technology company, PT Cicil Solusi Mitra Teknologi. In 2019-2021, PT Cicil Solusi Mitra Teknologi experienced a decrease in revenue, so the company must maintain its existence by using the right marketing strategy to increase its revenue. In addition, the coverage is still at 62,24% for cities and 10,82% for campuses in Indonesia that have just accessed it. This study analyses the right marketing strategy recommended to companies to overcome these problems. This research uses SOAR methods and the QSPM matrix to produce several alternative marketing strategies. The results of this study obtained an alternative strategy with the highest TAS score of 3,03, which is routinely holding attractive discount promotions at certain events regularly both to prospective users, users, and special members and maximizing to increase student interest in getting to know services and transacting in the future and this strategy becomes a top priority to be recommended in PT Cicil Solusi Mitra Teknologi.